STRATEGI MARKETING POLITIK AZHAR ABDURRAHMAN DALAM MEMENANGKAN PEMILU LEGISLATIF DPRA PERIODE 2019-2024 - Aminah Aminah (Journal of Political Sphere, 2020)
AbstractGeneral elections are one of the important instruments in measuring the quality of democracy implementation in a country. In winning the 2019-2024 period elections, various political marketing strategies began to be undertaken by every prospective candidate to either be done by the political party or by prospective candidates. This research was conducted to find out the strategy conducted by Ir. Azhar Abdurrahman in winning the 2019 elections and making it a member of DPRA. This method of research uses qualitative methods of descriptive. The Data needed in this writing was obtained through field research by interviewing the informant and monitoring the Facebook account on behalf of Ir. Azhar Abdurrahman. The results showed that the political marketing that was applied by Azhar Abdurrahman (1) Mapping the political market, (2) (2) A nominee of Aceh party for assembly at provincial, (3) Forming campaign teams consisted of former GAM team and (4) utilize social media Facebook. For that, the electoral participants can apply various forms of political marketing strategy in winning the elections.Keywords:Strategy, Marketing politics, and Elections